Analysis Of Hand, Legs, And Vertebra Movements When Doing Smash In Male Volleyball Athletes Of The Young Bahana Club In Malang - Yudhistianing Anugerah Ayu, Agashi; Yunus, Mahmud; Abdullah, Ahmad (Indonesian Conditioning Coaches, 2024)
This research aims to find out what angles are formed in the hands, feet and vertebrae when smashing. Smash is a hard or slow ball hit as part of an in-game attack designed to kill an opponent and score points. In this study there were 40 populations and used 10 samples, with sampling using the purposive sampling method. This research uses direct measurement experiments using the Dartfish application version 6.0.10406.0. By recording samples when performing a smash movement using 2 cameras taken on 2 sides, namely the left side and the back side. In this research, we will analyze the movement when performing a smash using the Dartfish application version 6.1.11102.0. After taking measurements by recording the smash movement, then make observations using the Dartfish application version 6.1.11102.0. This research shows that the results of the analysis show that there are differences between the results of the analysis that has been carried out and the parameters that have been studied previously. This occurs due to various factors, namely the habits of athletes during training, differences in playing styles for each athlete, flexibility in each athlete's vertebrae, and also differences in arm and leg movements for each athlete. From this research, the average analysis results showed that the right foot angle was 66°, the left foot angle was 47.87°, the hand angle was 89.67°, and the vertebral angle was 30.08°.